Hybrid Intelligence and Creative Economies - Lina Marlina (UDEX Institute, 2026)
Hybrid intelligence is redefining value creation in contemporary creative economies through the integration of human cognition and artificial intelligence. Creativity, innovation, and strategic capability increasingly emerge from distributed and interaction-based processes rather than isolated human agency. This transformation reshapes how organizations generate ideas, develop capabilities, and compete in dynamic environments. At the market level, authenticity and meaning are reconstructed through hybrid production systems, while ownership and responsibility become fragmented across multiple actors. Understanding these dynamics is essential for advancing theory and guiding practice in AI-mediated socio-technical systems.